Реконструкция процесса изготовления двусторонних микокских орудий - Весельский, А.П. (Археологический альманах, 2009)
Kabazi V, level III/4-2 produced the really rare archaeological object: the pit filled by debitage (2786 items), that is 44 flakes, 7 blades and 2735 chips. The 83 pieces were conjoined. The refits and their interpretations presented in this paper reflect some very important aspects of bifacial tool technology in the Crimean Micoquian. It appears that in the frame of the Micoquian techno-complex the technological approaches to raw material reduction were very variable. Aside from the well-known and characteristic plano-convex bifacials, Micoquian knappers were able to produce bifacial preforms with a bi-convex cross-section. On the other hand, there is no evidence of bi-convex retouching in the Crimean Micoquian; in spite of bi-convex preform shaping, tool retouching was undertaken using the typical plano-convex manner.